(untitled) (Proceedings of the International Conference of Geological Engineering Faculty, 2021)
The research in Pangandaran was due to the presence of exposed rock lithology and the presence of fossil content, either macrofossil or microfossil. Research sites are located at 108°27’46.55’’ to 108°30’29.88’’E and 7°41’35.54’’ to 6°38’53.60’’. This study was conducted to determine the distribution of foraminifera contained in the constituent sandstone units of the Bentang Formation. The research was conducted at 7 (seven) points of location of sandstone outcrops. Analysis and identification of foraminifera using a binocular microscope after foraminifera preparation. The distribution areas of the sandstone units of the study area are in the Cimanggu, Bula Krandu and Karangbenda areas. Age datum markers that are characterized by planktonic foraminifera fossils, namely Sphaerodinellopsis multilobe and Globigerinoides ruber. Benthic foraminifera dominated by Lenticulina suborbicularis, Nouvigerina ampulaceae, Cibicides tenuimargo, Anomalinoides globulosus, Heterolepa praecincta, Ammonia convexa reflects a shallow marine bathymetry zone or mid neritic (50-100m). Based on the content of planktonic and bentonic foraminifera, the sandstone units of the Bentang Formation were deposited during the Middle Miocene (N12-N13) age in a shallow marine depositional environment